Verrucous carcinoma of vulva - Kabir, N; Ara, I; Ahmed, A; Muhsin, AU (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S53-56The abstract of this article is available on the PubMed website